Iron Seller Activities in Riverbank Communities in South Kuin Village - Radjikan, Febrian Putra Anugrah; Syaharuddin, Syaharuddin; Handy, Muhammad Rezky Noor; Nur’aini, Fatwa; Rusmaniah, Rusmaniah (Journal of Social Development, 2024)
The background of the iron sellers in the riverbank is a human unit or group of people living in along the riverbank.  Their lives are dominated by river culture.  However, the life of the Bantaran Sungai community in Kuin Selatan Village, Banjarmasin, gives a different and very interesting nuance.  There are forms of economic activity in the area that indirectly do not influent in the river for the spring of life, but present a complete form of economic activity, both from production and distribution and consumption activities.  This is reflected in the economic activity of iron craftsmen. The points at this research were: (1.) To discover out what kinds of goods were made by iron sellers in Kuin Selatan Village, (2.) To find out the making, marketing and usage activities take out by iron sellers at Kuin Selatan Village, (3.) To discover out the ways of making iron by iron sellers. Descriptive qualitative method was used in the research to illustrate the economic activities of the riverbank groups in Kuin Selatan Village.  The person in this research were iron craftsmen.  The research instrument consisted of observation guides and interviews made by the researchers themselves.  The data analysis technique used is data reduction, data presentation and conclusion.  Test the validity of the data using time triangulation, sources and data collection techniques.The conclusions appear that the interesting economic activity of the riverbank groups in Kuin Selatan Town was ironmonger.  Its economic activities contain: (1.) production activities, (2.) marketing activities, (3.) usage activities.  The making activities of the iron craftsmen are in the form of agricultural tools such as hoes, crowbars, machetes, sickles, and also in the form of household utensils such as frying pans, knives and panicles.  In addition, other products include bolts, drills, truck elbows, hinges, valves, drums and containers.  Distribution activities can be seen in the acquisition of raw materials and distribution of production results to consumers.  The form of distribution of goods is carried out directly or indirectly.  Obtaining nail materials indirectly through collectors, while the distribution of manufactured goods through agents.  The consumption activities of iron craftsmen are carried out directly, namely buyers come directly to the craftsmen to buy the goods they produce and indirectly, namely traders buy to be resold to the market to consumers. The conclusion reached by these iron sellers is that we can get to know the processing of iron goods which can be made into several kinds of tools to break down gold such as drums and valves for example, accompanied by activation of production, distribution and consumption